Penerapan Media Smart Box Untuk Meningkatkan Partisipasi Peserta Didik Pada Mata Pelajaran Pendidikan Pancasila di MIN 1 Gresik - Alifa Nur Laili; Riysdatur Rosyidah; Raden Syaifuddin; Hidayatul Annisak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the application of Smart Box media in Pancasila Education learning for grade 1 students of MIN 1 Gresik and its influence on increasing student participation. Smart Box media is an interactive game-based media that contains material explanations, classification activities, and spinner quizzes, specifically designed to introduce the values of mutual cooperation in a fun and concrete way. The method used is descriptive qualitative, with data collection through observation and documentation of learning activities. The results of the study showed that Smart Box media was able to arouse students' interest, enthusiasm, and active involvement. Students seemed enthusiastic about participating in activities, both in playing Smart Box and when working on LKPD. The use of this media has a positive impact on creating a lively learning atmosphere, increasing understanding of the material, and encouraging individual student involvement. Thus, Smart Box has proven to be an effective media in instilling Pancasila values through a contextual and fun learning approach.